Hybrid membrane processes for water reuse - Pidou, Marc (Cranfield University, 2006)
Water recycling is now widely accepted as a sustainable option to respond to the general increase of the fresh water demand, water shortages and for environment protection. Because greywater represents up to 70% of domestic wastewater volume but contains only 30% of the organic fraction and from 9 to 20% of the nutrients (Kujawa-Roeleveld and Zeeman, 2006), it is seen as one of the most appropriate sources to be treated and reuse. A broad range of technologies has been used for greywater recycling including soil filters (Itayama et al., 2004), membranes (Ahn et al., 1998) and biological aerated filters (Surendran and Wheatley, 1998). However, at small scale, such as individual household, the variability in strength and flow of the greywater and potential shock loading affect the efficacy of biological technologies. Moreover, simple physical processes, efficient to reduce the physical pollution within the greywater, are often limited to degrade the organic fraction (Jefferson et al, 2000). There is then a need for alternative technologies that would not be affected by such problems and that could provide the treatment required for reuse. This project investigated the potential of alternative technologies for greywater recycling. Four chemical systems, coagulation, MIEX®, adsorption and membrane chemical reactor based on an advanced oxidation process (TiO2/UV), were assessed at bench scale. Coagulation and MIEX® were found to achieve a limited treatment of the greywater and consequently to be not suitable in case of strict reuse standards. Whereas, adsorption with activated carbon and membrane chemical reactor provided a very good treatment of the greywater with an advantage to the advanced oxidation process as it could meet the strictest standard for reuse for BOD, turbidity and suspended solids as well as for the total and faecal coliforms. Following this results the membrane chemical reactor was tested at pilot scale and compared to a benchmark system, a membrane bioreactor. Both systems achieved a very good treatment of the greywater; however, the MBR was found to be a more robust technology with all the samples tested for BOD and turbidity below the most stringent standards. The main difference between the two systems was observed in terms of the hydraulic conditions. Indeed, important membrane fouling was occurring in the MCR. A more detailed study of membrane fouling in the MCR was carried out for a better understanding of the phenoma occurring. It was found that little fouling occurred when TiO2 was dispersed in clean water. Alternatively, a significant fouling could be observed when TiO2 was coated with specific products suggesting that a reaction occurs when TiO2 is in solution with particular chemicals changing its fouling propensity. Overall, the MBR was found to be the best technology in terms of performance and robustness. However, it was also found that spiking of domestic products can alter its performance due to their toxicity. Chemical systems, which are not affected by toxicity, seem to be a good alternative to biological systems. However, none of the systems tested here could match the effluent quality achieved by the MBR. Alternatively, the MCR achieved good treatment performance and limitation of the membrane fouling would make it a very good alternative.